Indexes of Aortic Pressure Augmentation Markedly Underestimate the Contribution of Reflected Waves Toward Variations in Aortic Pressure and Left Ventricular Mass. Issue 3 (March 2015) - Booysen, Hendrik L.; Woodiwiss, Angela J.; Sibiya, Moekanyi J.; Hodson, Bryan; Raymond, Andrew; Libhaber, Elena; Sareli, Pinhas; Norton, Gavin R.
Abstract : Although indexes of wave reflection enhance risk prediction, the extent to which measures of aortic systolic pressure augmentation (augmented pressures [Pa] or augmentation index) underestimate the effects of reflected waves on cardiovascular risk is uncertain. In participants from a community sample (age >16), we compared the relative contribution of reflected (backward wave pressures and the reflected wave index [RI]) versus augmented (Pa and augmentation index) pressure wave indexes to variations in central aortic pulse pressure (PPc; n=1185), and left ventricular mass index (LVMI; n=793). Aortic hemodynamics and LVMI were determined using radial applanation tonometry (SphygmoCor) and echocardiography. Independent of confounders, RI and backward wave pressures contributed more than forward wave pressures, whereas Pa and augmentation index contributed less than incident wave pressure to variations in PPc ( P <0.0001 for comparison of partial r values). In those <50 years of age, while backward wave pressures (partial r =0.28, P <0.0001) contributed more than forward wave pressures (partial r =0.15, P <0.001; P <0.05 for comparison of r values), Pa (partial r =0.13, P <0.005) contributed to a similar extent as incident wave pressure (partial r =0.22, P <0.0001) to variations in LVMI. Furthermore, in those ≥50 years of age, backward wave pressures (partial r =0.21, P <0.0001), but not forward wave pressures ( P =0.98), while incident wave pressure (partial r =0.23, P <0.0001), but not Pa ( P =0.80) were associated with LVMI. Pa and augmentation index underestimated the effect of wave reflection on PPc and LVMI in both men and women. Thus, as compared with relations between indexes of aortic pressure augmentation and PPc or LVMI, strikingly better relations are noted between aortic wave reflection and PPc or LVMI. Abstract : Supplemental Digital Content is available in the text.